Kasih Sayang sebagai Konsep Hablumminannas dalam Perspektif Hadis: Studi Takhrij dan Syarah Hadis - Ia Aulia (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about hablumminannas. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about hablumminannas in the narration of Imam Shahih Bukhari No. 6828. The results and discussion of this study indicate that the status of the hadith is hasan li ghairihi which meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the Hadith narration of Imam Bukhari No. 6828 is relevant to be used as a struggle to strengthen human relations with humans on the basis of compassion.